Analysis of the Significance and Applications of Drugs Affecting Nicotine-Sensitive Cholinergic Receptors in Medical Practice - oʻgʻli, Sokhib Rashidov Zamon; qizi, Khilola Musaeva Usmonqul; qizi, Barchinoy Abdulmurodova Dilshod (American Journal of Bioscience and Clinical Integrity, 2025)
In terms of brain development, physiology, and pathology, the cholinergic system is crucial. Here, we go over how some changes in this system, such as genetic mutations or aberrant receptor function, might result in defective brain circuitry that causes illness. The nicotinic acetylcholine receptor (nAChR) and its involvement in addiction, neuropsychiatric and neurodegenerative disorders, and epilepsy are the main topics of the review. Cholinergic dysfunction is linked to inflammatory processes primarily through the interaction of peripheral immune cells and brain-expressed α7 nAChRs. Research indicates that diseased conditions are triggered and exacerbated by these neuroinflammatory processes. We go over the preclinical data showing that nAChR ligands have therapeutic potential in treating autosomal dominant sleep-related hypermotor epilepsy, Parkinson’s disease, Alzheimer’s disease, and schizophrenia spectrum disorders. In both human and animal models, nicotinic acetylcholine receptor (nAChR) activation improves sensory-cognitive performance; however, the underlying brain mechanisms are still unclear. Recent research on the nicotinic modulation of neuronal processing in the cerebral cortex that suggests possible pathways underpinning improved cognitive function is compiled in this article. Studies from our laboratory focus on nicotinic modulation of auditory cortex and consequences for auditory–cognitive processing, although relevant emerging discoveries from multiple brain locations are highlighted. Recent findings suggest additional, possibly significant contributions from α2 subunits that are relatively rare in cortex, despite the well-established important contributions of the prevalent nAChRs with α7 (homomeric receptors) or α4 and β2 (heteromeric) subunits. The goal of ongoing research is to clarify the distinct roles that various nAChRs play in cognitive and cortical function.